Improvement of motorcycle suspension test set-up / Mohd Zaki Bahrom - Bahrom, Mohd Zaki (2003)
This project is about the improvement of the Motorcycle Suspension Test Setup and the vibration test on the motorcycle suspension performance using the new test rig. The testing was conducted on the motorcycle which has complete parts to find the effect of adding Palm Oil to the Fork Oil in different proportions. The viscosity tests are also conducted to find the viscosity of fork oils having different percentages of palm oil (0%, 10%, 30%, 50%, 70%, 90% and 100%). Linear bearing are used to guide the motorcycle in the vertical direction during testing. A platform is provided in the testing, so that the motorcycle can be easily fixed for testing. The advantages of the improved test set-up over the earlier test set-up are highlighted. The performance of Fork Oil containing 10% Palm Oil is found to perform better compared to other combination tested.